Antiretroviral Treatment Failure and Associated Factors Among HIV-Infected Children on Antiretroviral Therapy: A Retrospective Study - Getawa S (Dove Medical Press, 2021)
Solomon Getawa,1 Abaynesh Fentahun,2 Tiruneh Adane,1 Mulugeta Melku1 1Department of Hematology and Immunohematology, School of Biomedical and Laboratory Sciences, College of Medicine and Health Sciences, University of Gondar, Gondar, Ethiopia; 2Department of Clinical Pharmacy, School of Pharmacy, College of Medicine and Health Sciences, University of Gondar, Gondar, EthiopiaCorrespondence: Tiruneh AdaneDepartment of Hematology and Immunohematology, School of Biomedical and Laboratory Sciences, College of Medicine and Health Sciences, University of Gondar, EthiopiaP. O. BOX: 196 Tel +251-949-914-917Email tirunehadane01@gmail.comBackground: HIV/AIDS-associated morbidity and mortality have reduced since the introduction of antiretroviral therapy (ART). Treatment failure is one of the causes of mortality, morbidity, and the development of drug-resistant viral strains. Therefore, this research aims to assess the prevalence and associated factors of treatment failure among children with HIV/AIDS on antiretroviral therapy attending the University of Gondar Specialized Referral Hospital, Northwest Ethiopia.Methods: A retrospective study was conducted on 200 children registered for ART from 2005 to 2017. Data regarding patients’ socio-demographic, baseline clinical characteristics, and treatment-related information were collected through a review of their medical records. Data were entered into Epi-info version 3.5.3 and analyzed using statistical package for social sciences (SPSS) version 21 software. To summarize characteristics of the study participant’s descriptive statistics were done. Bivariable and multivariable binary logistic regression were fitted to identify factors associated with treatment failure. The odds ratio and 95% confidence interval (CI) were calculated to assess the strength of the association and P-value< 0.05 in the multivariable regression was considered as statistically significant.Results: The prevalence of ART failure was 12.5% (95% CI: 7.88, 17.12), clinical failure was the most common followed by immunologic failure with only a small proportion having both clinical and immunologic failure. The mean time to develop treatment failure after initiation of the first-line regimen was 22.28 ± 24.00 months. Being male (AOR= 3.15; 95% CI: 1.18– 8.39), co-infected with tuberculosis (TB) at baseline (AOR= 2.37; 95% CI: 1.23– 8.84), being on ART for a long period (> 36 months) (AOR= 1.01; 95% CI: 1.34– 2.89), and regimen change (AOR=9.22; 95% CI: 3.36– 25.03) were factors of ART failure.Conclusion: In this study, there is significant treatment failure among HIV-infected children. Having co-infection, being on ART for a long period, regimen change, and being male were found to be independent factors of treatment failure in children. Therefore, timely identification and monitoring of ART failure should be necessary to enhance the benefit and to prevent further complications. Prophylaxis for opportunistic infections such as co-trimoxazole preventive therapy should continue to recover the immunological status of the child.Keywords: HIV/AIDs, antiretroviral, treatment failure, associated factors, Ethiopia